MODERN APPROACHES TO SPECIALIZED PHARMACEUTICAL CARE FOR PATIENTS WITH ONCOLOGICAL DISEASES - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Ольга Владимировна Хорошилова; Виктор Андреевич Семенихин; Ирина Герасимовна Танцерева (Медицина в Кузбассе)
A review of analytical materials on the state of sanitary and epidemiological well-being of the population in the Russian Federation and in Kuzbass (2017-2021) showed that in the field of public health protection, health-saving technologies based on specialized pharmaceutical assistance to the population carried out in determining the individual integrative risk of developing non-communicable diseases, in particular oncological, allowing planning are internationally recognized and most effective. and to carry out their prevention.